FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKS REMAJA DI DESA PASSO KECAMATAN BAGUALA KOTA AMBON - Bazrul Makatita; Herlina; Stevanus Maspaitela (Pasapua Health Journal, 2022)
Introduction. The rapid development of the times has made foreign culture influence teenagers, especially teenagers who follow negative cultural trends, the use of social media also affects adolescent sexual behavior seen from sexual information that circulates quickly and widely, and that is coupled with the role of peers who negative influence makes adolescents at risk of sexual behavior. Method. This research uses a type of analytic survey research, with a cross-sectional study design. The sampling technique in this study used a total sampling technique with a total of 76 respondents. Results. In this study, the chi-square test statistical test was used and the results obtained were 28 (71.8%) respondents who were influenced by a foreign culture with risky sexual behavior, 13 (35.1%) respondents who were not affected but were at risk of sexual behavior. Then those affected by social media and at risk of sexual behavior were 32 (88.9%) respondents, respondents who were not affected but at risk of sexual behavior were 9 (22.5%) respondents. Those who are influenced by peers and are at risk of sexual behavior are 27 (90.0%), those who are not affected but are at risk are 14 (30.4%). With a significant value p= p=<0.05 (p=0.000). Conclusion. Based on the results of statistical tests using chi-square, it was obtained p value = <0.05, it can be concluded that there is a relationship between foreign culture and adolescent sexual behavior in Passo Village, Baguala District, Ambon City, there is a relationship between social media and adolescent sexual behavior in Passo Village. Baguala District, Ambon City, and there is a relationship between peers and adolescent sexual behavior in Passo Village, Baguala District, Ambon City.